Changing prognosis in paroxysmal nocturnal haemoglobinuria disease subcategories: an analysis of the International PNH Registry. Issue 9 (16th September 2016) - Socié, G.; Schrezenmeier, H.; Muus, P.; Lisukov, I.; Röth, A.; Kulasekararaj, A.; Lee, J. W.; Araten, D.; Hill, A.; Brodsky, R.; Urbano‐Ispizua, A.; Szer, J.; et al.
Abstract : Background: Paroxysmal nocturnal haemoglobinuria (PNH) is a rare disease. Although much progress has been made in the understanding of the pathophysiology of the disease, far less is known with respect to the clinical outcomes of patients with PNH. Few retrospective studies provide survival estimates, and even fewer have explored the clinical heterogeneity of the disease. Haemolytic and aplastic anaemia (AA) forms of the disease have been recognised as main disease categories, with the haemolytic form being associated with the worst prognosis by the largest studied cohort some years ago. Aims: To describe mortality and causes of death in PNH overall and by PNH classification and to evaluate risk factors associated with mortality. Methods: We analysed data of 2356 patients enrolled in the International PNH Registry with multivariate analyses, using time‐dependent covariates. Patients were classified into haemolytic, AA/PNH syndrome or intermediate PNH. Results: Overall, 122 (5.2%) patients died after enrolment, the incidence according to subcategories being 5.1, 11.7, 2.0 and 4.8% for patients with haemolytic PNH, AA‐PNH, intermediate and insufficient data respectively. Older age and decreased performance status also affected survival in multivariate analysis. Improved outcome of patients with haemolytic PNH suggests that eculizumab treatment in PNH may be associated with improved survival. Conclusion: A detailed analysis of clinical presentations and causes of death in patients with PNH, overall and by disease subcategories, provide evidence that in the current era, patients with haemolytic PNH are no longer those who harbour the worst prognosis. This finding differs sharply from what has been previously reported.